Analisis Peran Etika Bisnis Islam Dalam Membangun Strategi Loyalitas di UMKM Berbasis Syariah Kabupaten Pekalongan Pada Era Revolusi Industri 5.0 - Dinda Safira; Nur Zalfa Rifqo Nabila; Ahmad Zaeni Ismail; Karomatul Izzah; Dwi Novaria Misidawati (Yayasan Cendekia Gagayunan Indonesia, 2025)
Business ethics are studied not only to find out what business ethics are, but business ethics aims to help business actors make ethical business decisions. The purpose of this study is to determine the role of business ethics in building loyalty strategies in sharia-based MSMEs in Pekalongan Regency in the era of the 5.0 industrial revolution. The method used is descriptive qualitative, data sources come from interviews, observations and literature studies. The results of the study indicate that the application of Islamic business ethics principles can increase consumer loyalty through transparency, honesty, and ethical commitment in running a business. Factors that influence the application of Islamic business ethics in building loyalty strategies for sharia-based MSMEs in Pekalongan Regency are factors of belief, local culture and social norms, market pressure, and limited resources. Despite facing many challenges, trust and loyalty from consumers and better relationships with stakeholders are positive results felt by sharia-based MSMEs in Pekalongan Regency that apply Islamic business ethics. This shows that although the application of Islamic business ethics requires great effort and commitment, the long-term benefits in terms of sustainability and blessings are greater than unethical business practices.